Emotion detection for Bangla language - Rushan, Rowshan Rahman; Hossain, Sazid; Shovon, Shams Shahariar; Rahman, Md Arafat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.